UVC Sterilization Robot With Remote Wireless Mode and Autonomous Mode - Nanda Ferdana; Deska Insani Zaidarlis; Rahmalisa Suhartina; Andito Prasetya (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2022)
Public concerns during the coronavirus disease (COVID-19) pandemic in Indonesia, which began in early 2020 until now, are of particular concern. It is caused by the SARS-CoV-2 which can be spread by direct contact such as aerosols. In an effort to prevent and handle the spread of coronavirus, especially indoors, it can be done by disinfection and using ultraviolet-C (UVC) light sterilization. The use of UVC light sterilizers generally requires the operator to move the tool in the sterilization process, this fact is a concern because the operator must ensure the area can be exposed to UVC rays. This issue is what the author created to be able to design a UVC sterilization robot that can be controlled by wireless remote mode and autonomous mode in the hope of being able to sterilize the room properly controlled by the camera and seen from the control area using assistance. The design of the UVC robot for wireless remote mode and autonomous mode using Arduino UNO as a microcontroller, ESPCAM-32 as a camera function that is integrated with wifi connectivity, HC-SR04 sensor to detect the distance of the tool with its surroundings, battery, navigated robot using the blynk application and the BTS 7960 motor driver as a motor for the tool wheel. The UVC sterilization robot was tested by testing the function of the remote control mode, testing the autonomous mode and the function of the UVC lamp. From the results of the tests and analysis performed, the UVC disinfection robot can work well in both the wireless remote mode and the autonomous mode. UVC robot sterilization can be used mobile and automatically and can make it easier for operators to carry out sterilization in the room.